Formulating Seismic Intensity Scale (JMA-SIS) Using Response Spectrum: A New Approach for Structural Engineering Design - Nanang Gunawan Wariyatno; Ay Lie Han; Yanuar Haryanto; Gathot Heri Sudibyo; Sumiyanto; Nastain; Arwan Apriyono; Laurencius Nugroho; Hsuan-Teh Hu; Fu-Pei Hsiao; Buntara Sthenly Gan (Advances in Technology Innovation, 2025)
This study aims to formulate a calculation for earthquake shaking intensity (rs_mSIS) based on the response spectrum (RS) using the Japan Meteorological Agency-seismic intensity scale. The research investigates the relationship between the response spectrum parameters—period and maximum acceleration—and the earthquake source types, including megathrust, Benioff, and shallow crust/background sources. Artificial ground motions are generated and analyzed using Matlab to calculate shaking intensity values, which are then used to develop the rs_mSIS formula. The formulation is validated against actual response spectrum data from 15 Indonesian cities and demonstrated high accuracy, with the Wariyatno coefficient applicable across all models. This approach provides a standardized method to assess seismic intensity, offering enhanced reliability for building design in earthquake-prone areas and serving as a valuable tool for engineers and urban planners to improve earthquake resilience in diverse seismic environments.